relationship Between Two Methods Of Perceived Exertion (session - Rpe, Exercise - Rpe) To Evaluate The Training Load Of Amateur Soccer Players In The Physical Preparation Phase - Noui , Larbi; Neghal , Mohamed (Journal of Sport Science Technology and Physical Activities, 2020)
This study aims to determine the relationship between two evaluation methods of training load through some aerobic and anaerobic training sessions during the physical preparation phase for football players (Session - RPE, Exercise - RPE). The researcher used the descriptive method. The sample was chosen intentionally and consisted of under 20 years 10 players from Najm Ain Oulmene football team (E.S.A.O), The activists at the level of the first regional section of the Constantine League, we used to collect data for the estimation scale (Session - RPE, Exercise - RPE) and the method The statistic used in the research was Pearson correlation coefficient and linear regression analysis. Results showed a strong correlation during aerobic trainings, while we found an average correlation during anaerobic trainings, and on this basis, we recommend that attention be paid to evaluating the training load by different (RPE) method